Jordlöparfaunan i bestånd av contortatall (Pinus contorta) och svensk tall (P. sylvestris) 1987 och 2010 - Borgstrand, Emma; Videkull, Li (SLU/Dept. of Forest Ecology and Management, 2012)
In the 1970´s the North American lodgepole pine (Pinus contorta) was introduced to Sweden in large scale. The lodgepole pine affects its new environment different from Scots pine (P. sylvestris), leading to a change in biological diversity.